Hydrous magmatism triggered by assimilation of hydrothermally altered rocks in fossil oceanic crust (northern Oman ophiolite). (1st August 2013) - France, Lydéric; Ildefonse, Benoit; Koepke, Juergen
Abstract : [1] Mid‐ocean ridges magmatism is, by and large, considered to be mostly dry. Nevertheless, numerous works in the last decade have shown that a hydrous component is likely to be involved in ocean ridges magmas genesis and/or evolution. The petrology and geochemistry of peculiar coarse grained gabbros sampled in the upper part of the gabbroic sequence from the northern Oman ophiolite (Wadi Rajmi) provide information on the origin and fate of hydrous melts in fast‐spreading oceanic settings. Uncommon crystallization sequences for oceanic settings (clinopyroxene crystallizing before plagioclase), extreme mineral compositions (plagioclase An% up to 99, and clinopyroxene Mg # up to 96), and the presence of magmatic amphibole, imply the presence of a high water activity during crystallization. Various petrological and geochemical constraints point to hydration, resulting from the recycling of hydrothermal fluids. This recycling event may have occurred at the top of the axial magma chamber where assimilation of anatectic hydrous melts is recurrent along mid‐ocean ridges or close to segments ends where fresh magma intrudes previously hydrothermally altered crust. In ophiolitic settings, hydration and remelting of hydrothermally altered rocks producing hydrous melts may also occur during the obduction process. Although dry magmatism dominates oceanic magmatism, the dynamic behavior of fast‐spreading ocean ridge magma chambers has the potential to produce the observed hydrous melts (either in ophiolites or at spreading centers), which are thus part of the general mid‐ocean ridges lineage. Key Points: Hydrous magmatism is part of the general mid‐ocean ridges lineage Hydrous component is introduced through assimilation of anatectic hydrous melts Processes able to trigger recycling are presented